EP.TH.177Safety profile of SurgiMend Acellular Dermal Matrix and Mentor implant assisted immediate breast reconstruction – Our experience at the Princess Royal University Hospital. (28th October 2021) - Shaaban, Gamal; Khan, Maryam; Ragad, Lilia; Norman, Carol; Kasem, Abdul; Uhercik, Michal
Abstract: Background: ADM (Acellular Dermal Matrix) assisted implant-based immediate breast reconstruction (IBR) is a common technique worldwide. Various ADMs are available manufactured from different sources. The Surgimend ADM (fetal bovine dermis) is fenestrated and rich in type I/III collagen; it is claimed to reduce fluid accumulation and promote healing. Methods: Retrospective observational analysis exploring safety profile using combination of SurgiMend MacroPorous (MP)/SurgiMend PRS and Mentor CPG/Mentor Siltex implants between January 2018 to December 2019. Patients with unilateral/bilateral IBR following Nipple sparing (NSM) or Skin sparing mastectomy (SSM) were included. The primary outcome was minor complications (seroma (>100ml on USS), hematoma, wound infection and infected seromas). Secondary outcome was major complications (flap necrosis, capsular contracture, implant explantation and Red Breast Syndrome). Results: Six (16.2%) bilateral and 31 (83.8%) unilateral IBR were performed in 37 patients. Mean age was 53.78 years. No major complications were recorded. Conclusions: The Surgimend ADM and Mentor implant combination demonstrate a good safety profile. Higher rates of seroma in this study could be explained by overdiagnosis and treatment at our unit, which in turn might imply as a result that no major complications were detected and no implant loss.